Single Incision Laparoscopic and Transanal Colorectal Surgery - Law, Wai Lun; Delaney, Conor P. (Springer New York : Imprint: Springer, 2014)
Single Incision Laparoscopic and Transanal Colorectal Surgery provide a comprehensive and state-of-the art review of single incision laparoscopic and transanal colorectal surgery. The text concentrates on surgical techniques and tricks in single incision laparoscopic and transanal surgery with detailed descriptions of the techniques, as well as indications and limitations of the procedures. The newly available evidence on these procedures is emphasized and all procedures are richly illustrated with diagrams and photos. Written by experts in their fields,  Single Incision Laparoscopic and Transanal Colorectal Surgery is a valuable resource for general surgeons, colon and rectal surgeons, laparoscopic GI surgeons, surgical residents and fellows in training interested in these two rapidly developing fields in colorectal surgery.